Accelerating datapath merging by task parallelisation on multicore systems. Issue 5 (3rd September 2019) - Fazlali, Mahmood; Fallah, Mohammad K.; Hosseinpour, Naemeh; Katanforoush, Ali
ABSTRACT: Datapath merging is an efficient approach to reduce hardware resources and configuration time in the synthesis of digital systems. In order to solve datapath merging, we have to find the maximum weighted clique, which is an NP-hard problem. So, datapath merging is a time-consuming process. In this article, we use OpenMP library to perform divide and conquer task parallelism to find the maximum weighted clique. Therefore, considerable reduction in the synthesis time and almost linear speedup has been achieved. The experimental results obtained from running this algorithm on different benchmarks represent speedup ranging from 1.2 times to 6.5 times for an 8-core system.